2014
DOI: 10.1021/jp501539z
|View full text |Cite
|
Sign up to set email alerts
|

From Molecular Dehydration to Excess Volumes of Phase-Separating PNIPAM Solutions

Abstract: For aqueous poly(N-isopropyl acrylamide) (PNIPAM) solutions, a structural instability leads to the collapse and aggregation of the macromolecules at the temperature-induced demixing transition. The accompanying cooperative dehydration of the PNIPAM chains is known to play a crucial role in this phase separation. We elucidate the impact of partial dehydration of PNIPAM on the volume changes related to the phase separation of dilute to concentrated PNIPAM solutions. Quasi-elastic neutron scattering enables us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
111
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(125 citation statements)
references
References 46 publications
14
111
0
Order By: Relevance
“…The water properties in these systems were studied theoretically [10] and experimentally by means of NMR [99], spectroscopy (e.g. FTIR) [59] and also quasielastic neutron scattering [73].…”
Section: Introductionmentioning
confidence: 99%
“…The water properties in these systems were studied theoretically [10] and experimentally by means of NMR [99], spectroscopy (e.g. FTIR) [59] and also quasielastic neutron scattering [73].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the molecular weight of monomer NIPAM (113.18), the number of bound water on each monomer n is obtained as shown in the inset, reducing from 34 to 3 with the increasing of temperature. This value is greater than the number of hydrated number in previous studies of PNIPAM chain (11‐0 of Shikata and coworkers and 8‐2 of Philipp et al), suggesting that for microgel networks the bound water not only includes the water molecules that bond to the monomer, but also includes the water molecules that are bound in the network. This difference reveals that the dynamics of the water molecules which do not interact with PNIPAM but are limited in the network is also different from that of the bulk water.…”
Section: Resultsmentioning
confidence: 59%
“…This result is close to the value of 13 obtained from differential scanning calorimetry by Shibayama et al Kogure et al quantitatively evaluated the hydration number bound to one NiPAM monomer in PNIPAM gel by ultrasonic velocity and found that the hydration number at low and high temperatures were about 7.5 (20 °C) and 3 (40 °C), respectively. By quasielastic neutron scattering method, Philipp et al revealed that the PNIPAM chain is partially dehydrated and the hydration number decreases from 8 to 2 during the phase transition. As can be seen from the above researches, most of these studies concentrate on the dehydration dynamics of the linear PNIPAM chain, and rarely involves the microgel.…”
Section: Introductionmentioning
confidence: 99%
“…On the molecular level, the phase separation is accompanied by a coil-to-globule transition and dehydration of the polymer chains. 2 A comprehensive overview of the various demixing scenarios and a compilation of relevant literature can be found in the introductory section of ref 3.…”
Section: Introductionmentioning
confidence: 99%